Shallow and Deep Trap State Passivation for Low-Temperature Processed Perovskite Solar Cells - Azmi, Randi; Nurrosyid, Naufan; Lee, Sang-Hak; Al Mubarok, Muhibullah; Lee, Wooseop; Hwang, Sunbin; Yin, Wenping; Tae Kyu Ahn; Kim, Tae-Wook; Ryu, Du Yeol; Do, Young Rag; Jang, Sung-Yeon (AMER CHEMICAL SOC, 2020)
While perovskite solar cells (PSCs) have emerged as promising low-cost solar power generators, most reported high-performance PSCs employ electron transport layers (ETLs, mainly TiO2) treated at high temperatures (>= 450 degrees C), which may eventually hinder the development of flexible PSCs. Meanwhile, the development of low- temperature processed PSCs (L-PSCs) possessing performance levels comparable to those of high-temperature processed PSCs has actively been reported. In this study, L-PSCs with improved long-term stability and negligible hysteresis were developed through the effective passivation of shallow and deep traps in organic-inorganic hybrid perovskite (OIHP) crystals and at the ETL/OIHP interface. L-PSCs with alkaline chloride modification achieved state-of-the-art performance among reported L-PSCs (power conversion efficiency (PCE) = 22.6%) with a long-term shelf life. The origin of long-term stability and the efficient passivation of deep traps was revealed by monitoring the trap-state distribution. Moreover, the high PCE of a large-area device (21.3%, 1.12 cm(2)) was also demonstrated, confirming the uniformity of the modification.